Regulation of primordial follicle formation, dormancy, and activation in mice - Go NAGAMATSU (The Society for Reproduction and Development, 2021)
In female reproduction, the oocyte number is limited after birth. To achieve a continuous ovulatory cycle, oocytes are stored in primordial follicles. Therefore, the regulation of primordial follicle dormancy and activation is important for reproductive sustainability, and its collapse leads to premature ovarian insufficiency. In this review, we summarize primordial follicle development and the molecular mechanisms underlying primordial follicle maintenance and activation in mice. We also overview the mechanisms discovered through in vitro culture of functional oocytes, including the establishment of primordial follicle induction by environmental factors, which revealed the importance of hypoxia and compression by the extra cellular matrix (ECM) for primordial follicle maintenance in vivo.